Swiss Feline Cancer Registry: A Retrospective Study of the Occurrence of Tumours in Cats in Switzerland from 1965 to 2008. Issue 4 (November 2015) - Graf, R.; Grüntzig, K.; Hässig, M.; Axhausen, K.W.; Fabrikant, S.; Welle, M.; Meier, D.; Guscetti, F.; Folkers, G.; Otto, V.; Pospischil, A.
Summary: Cancer is one of the leading causes of death in companion animals. Information on the epidemiology of cancer is instrumental for veterinary practitioners in patient management; however, spontaneously arising tumours in companion animals also resemble those in man and can provide useful data in combating cancer. Veterinary cancer registries for cats are few in number and have often remained short-lived. This paper presents a retrospective study of tumours in cats in Switzerland from 1965 to 2008. Tumour diagnoses were coded according to topographical and morphological keys of the International Classification of Oncology for Humans (ICD-O-3). Correlations between breed, sex and age were then examined using a multiple logistic regression model. A total of 18, 375 tumours were diagnosed in 51, 322 cats. Of these, 14, 759 (80.3%) tumours were malignant. Several breeds had significantly lower odds ratios for developing a tumour compared with European shorthair cats. The odds of a cat developing a tumour increased with age, up to the age of 16 years,  and female cats had higher risk of developing a tumour compared with male cats. Skin (4, 970; 27.05%) was the most frequent location for tumours, followed by connective tissue (3, 498; 19.04%), unknown location (2, 532; 13.78%) and female sexual organs (1, 564; 8.51%). The most common tumour types were epithelial tumours (7, 913; 43.06%), mesenchymal tumours (5, 142; 27.98%) and lymphoid tumours (3, 911; 21.28%).